IIMA's digital leap : formulating online education strategy - Verma, Sanjay, (SAGE Business. Cases., 2019)
Indian Institute of Management Ahmedabad (IIMA) was a leading management institute in India and Asia-Pacific. The popularity of online education in early 2000 also promoted the leadership team at IIMA to step in the domain of digital education. They considered it as a dynamic and opportunity-rich field that would encourage innovations and disruptions. Furthermore, online education also could help in reducing the issues faced by the management education sector in India like lack of skilled graduates, lack of qualified faculty in India, lack of quality control on management education curriculum, etc. Thus, an e-Learning Committee was formed in 2014 IIMA to formulate the online education strategy of the Institute. The case presents the options available for its online education.